SOCIO-PSYCHOLOGICAL CHARACTERISTICS OF SCHOOLCHILDREN'S MOTIVES FOR CHOOSING A PROFESSION. (Scientific journal of the Fergana State University, 2024)
This article theoretically substantiates the need to prepare high school students for choosing a profession, the role of motivational factors in choosing a profession, methods of forming internal motivational factors, as well as the socio-psychological characteristics of motivation for choosing a profession by schoolchildren. practically analyzed.